QUASI ONE DIMENSIONAL MODEL FOR DYNAMIC TUBES BLOOD ELASTIC - PITRIANA (NIM. 20910010); Pembimbing : Dr. Agus Yodi Gunawan, ELSA
Blood flow in arteries has a complex structure because this system involves blood flow, motion of muscle of the arteries, and return of outer pressure. One of methods that we can use for constructing a model for dynamics of elastic blood vessel is an approximate model, so called quasi one dimensional. This model is derived from the continuity equation and momentum equation. The model leads to a system of partial differential equations. In this thesis, we solved the equations both analytically and numerically. In the analytically part, we apply the D Alembert method such the reduced equation leads to the wave equation with external forces term. For numerical part, we use Discrete Morse Flow (DMF) method, a variational method based on the minimization of a time discretetized function. Result show that the numerical solution and analytic solution are both quite in agreements.